Clear cell mesotheliomas with inactivating VHL mutations and near‐haploid genomic features. Issue 5 (25th December 2022) - Michal, Michael; Kravtsov, Oleksandr; Ross, Jeffrey S.; Skanderová, Daniela; Martínek, Petr; Mosaieby, Elaheh; Mata, Douglas A.; Williams, Erik A.; Hung, Yin P.
Abstract: Clear cell mesothelioma is uncommon and shows predominance of clear cells with resemblance to clear cell carcinomas. Clinicopathologic and molecular descriptions of clear cell mesothelioma remained limited. In this study, we identified an index patient with clear cell mesothelioma, confirmed by immunohistochemical and ultrastructural studies. Targeted next‐generation sequencing revealed the presence of an inactivating VHL mutation. We then systematically searched for VHL ‐mutant mesotheliomas in a comprehensive genomic profiling database of 1532 mesotheliomas. Collectively, we identified a cohort of four VHL ‐mutant clear cell mesotheliomas, including three peritoneal and one pleural tumors from three females and one male, with age range of 47–68 (median 63) years. Histologically, each tumor showed a microcystic to tubulopapillary architecture with prominent clear cells. By next‐generation DNA sequencing, each of the four clear cell mesotheliomas harbored inactivating VHL mutations, while lacking other alterations typical of mesotheliomas such as BAP1, NF2, SETD2, CDKN2A, CDKN2B, TP53, and PTEN . By using low‐pass whole genome sequencing on the index case and targeted next‐generation sequencing on the remaining three cases, we identified extensive loss of heterozygosity throughout the genome but consistently sparing chromosomes 5, 7, and 20, characteristic of genomic near‐haploidization. In summary, clear cell mesotheliomas were characterized by inactivating VHL mutations and genomic near‐haploidization and appeared to represent a distinct clinicopathologic and molecular category of mesotheliomas. Our findings implicate VHL in the pathogenesis of a subset of mesotheliomas, particularly those with clear cell morphology.